El sector licorero del Ecuador frente a las medidas tributarias impuestas - Larrea Paredes, María de Lourdes (2018)
This research analysis the liquor sector which represents an important item of the Ecuadorian economy, it is composed of importers and local producers who in many casesneed the imported goods for their production. All the states seek to improve their tax collection for the execution of works or improvement of the services delivered to the citizenship, whit this purpose, Ecuador Government applied a series of taxes as VAT value added tax, special consumption tax ICE , tariffs on imports, safeguards, imposed on IR income, among others. The present study focused on the import sector by the series of tax measures applied since 2009to 2015, and analyze the performance of imports from its application. Tariffs, ICE, VAT, safeguards have reduced imports and affected the sale price of beverages and consumption in establishments.